BRAND POSITIONING DAN TRUST TERHADAP LOYALITAS NASABAH (STUDI PADA NASABAH BPR JTIM CABANG BATU) - Wijayana, Dona Pambudi (Journal of Innovation in Business and Economics, 2016)
The purpose of this study was to the positioning of brand loyalty , how positioning the brand to trust , how to trust in the loyalty and how to position the brand loyalty through customer confidence in their loan JATIM on Branch of Batu City. Sampling obtained from 100 respondents credit customers BPR Jatim on Branch of Batu City, studies using Patial Least Square ( PLS ) and the obtained results of research are positioning the brand effect on loyalty , positioning the brand effect on confidence , trust affect the loyalty and positioning the brand effect on loyalty through trust BPR JATIM on Branch of Batu City.Keywords: Brand Positioning, Loyalty, Trust